Quantitative analysis of mammalian GIRK2 channel regulation by G proteins, the signaling lipid PIP2 and Na+ in a reconstituted system - Wang, Weiwei; Whorton, Matthew R; MacKinnon, Roderick (eLife, 2014)
GIRK channels control spike frequency in atrial pacemaker cells and inhibitory potentials in neurons. By directly responding to G proteins, PIP2 and Na+, GIRK is under the control of multiple signaling pathways. In this study, the mammalian GIRK2 channel has been purified and reconstituted in planar lipid membranes and effects of Gα, Gβγ, PIP2 and Na+ analyzed. Gβγ and PIP2 must be present simultaneously to activate GIRK2. Na+ is not essential but modulates the effect of Gβγ and PIP2 over physiological concentrations. Gαi1(GTPγS) has no effect, whereas Gαi1(GDP) closes the channel through removal of Gβγ. In the presence of Gβγ, GIRK2 opens as a function of PIP2 mole fraction with Hill coefficient 2.5 and an affinity that poises GIRK2 to respond to natural variations of PIP2 concentration. The dual requirement for Gβγ and PIP2 can help to explain why GIRK2 is activated by Gi/o, but not Gq coupled GPCRs.
Keywords: G protein gated potassium channel; planar lipid bilayer; G protein; PIP2; sodium activation; G protein coupled receptor